The Legal Aspects of the UAE- Israel Peace Treaty - Al-Husseini, Loai Sameer (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to give an analytical reading for the provisions of the UAE- Israel Peace Treaty in accordance with the provisions of International Law. It also demonstrates the influence of the Treaty on the consistency of the Arab position toward the Palestinian Issue. Furthermore, the study reveals the similarities and differences between the UAE- Israel peace treaty and other international treaties signed between the Arab States and Israel in the light of the Israeli strategy based on the approval of Arab parliaments in all peace treaties aiming at a complete normalization at the level of both: official and popular and searching the contractual positions of the two parties of the Treaty as an international treaty subject to the provisions of International Law and the Vienna Convention and the Equality of Opportunity Principle between its two parties. The researcher uses the descriptive and analytical approach for the treaty provisions and the inductive approach for the aspects of the Arab- Israeli conflict. The study concludes that the Treaty has affected the Palestinian Issue and weakened the Arab embrace of the Issue and its dissipation of the decision of the Arab League to boycott Israel, which was agreed upon in the Arab Peace Initiative at Beirut Summit in 2002.